Hubungan Orientasi Karier dengan Optimisme pada Mahasiswa Jurusan Keagamaan UIN Sunan Gunung Djati Bandung - Tasya Augustiya; Qori Nurislamiaty; Muhammad Dasrais Al-fatoni; Lea Nurbayu Rachma (Jurnal Psikologi Islam dan Budaya, 2019)
The community's stigma regarding the low employment prospects of religious majors did not lower their optimism. They still feel optimistic because they already had an overview of their careers (career orientation). The study aims to examine the relationship between career orientation and optimism in students majoring in religion and how much the relationship between the two. This study used 2 instruments, namely the LOT-R scale to measure optimism and Career Maturity Inventory (CMI) to measure career orientation. Both of these scales are scales that have been adapted in Indonesia by previous researchers and have been modified by the researchers. The sample in this study was 98 students majoring in religion, which was collected by purposive sampling technique. The results of the study indicate that there is a relationship between career orientation and optimism.